BIJAK DALAM PENGGUNAAN INTERNET BAGI SISWA/I SMK YUPPENTEK 5 TANGERANG - Robby Alvian Jaya Mulia; Afriyanto; Alin Lestari; Andi Afif Nawawi; Anisa Maulida; Ardiana; Arief Kurniawan; Muhamad Mustofa Ramadhan; Muhammad Nawawi; Yayah Zakiyah; Rinna Rachmatika (Abdi Jurnal Publikasi, 2022)
The rapid advancement of internet technology without education on how to use it leads to internet addiction and a tendency to use the internet for harmful or even futile purposes, although there are also many positive sides. Therefore, we carry out this activity to guide students at SMK Yuppentek 5 Tangerang so that they use the internet in a useful direction, such as looking for learning information, as a place to work, or even as a place to start a business. From the method of implementing the activities that we do, namely by being carried out directly or face-to-face, the students of SMK Yuppentek 5 Tangerang are very enthusiastic and active in listening to the material given. Through this community service activity, students can understand how to maximize internet use in a positive direction and minimize negative use so that they can create smart and productive students for the future.